2013
DOI: 10.1042/an20130028
|View full text |Cite
|
Sign up to set email alerts
|

Pigment Epithelium-Derived Factor Reduces Apoptosis and Pro-Inflammatory Cytokine Gene Expression in a Murine Model of Focal Retinal Degeneration

Abstract: AMD (age-related macular degeneration) is a neurodegenerative disease causing irreversible central blindness in the elderly. Apoptosis and inflammation play important roles in AMD pathogenesis. PEDF (pigment epithelium-derived factor) is a potent neurotrophic and anti-inflammatory glycoprotein that protects the retinal neurons and photoreceptors against cell death caused by pathological insults. We studied the effects of PEDF on focal retinal lesions in DKO rd8 (Ccl2−/−/Cx3cr1−/− on C57BL/6N [Crb1rd8]) mice, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 58 publications
3
39
0
Order By: Relevance
“…The mice were anesthetized and injected subconjunctivally (at the 2-3 o'clock position) with 1, 2, 5, or 25 mg/mL bevacizumab (Avastin; Roche Pharma, Basel, Switzerland; 5 lL per eye) one, two, or four times (injection every 2 days). For the recovery experiment, mice were injected simultaneously with bevacizumab (5 mg/ mL) and recombinant mouse pigment epithelium-derived factor (PEDF; R&D, San Diego, CA, USA; 15 ng/lL, 5 lL per eye), nerve growth factor (NGF; R&D; 20 ng/lL, 5 lL per eye) or ciliary neurotrophic factor (CNTF; R&D; 10 ng/lL, 5 lL per eye), in accordance with previous reports [32][33][34] and our preliminary experiments. Normal saline (0.9% NaCl) was injected as vehicle control.…”
Section: Methods and Materials Subconjunctival Bevacizumab Injection mentioning
confidence: 89%
“…The mice were anesthetized and injected subconjunctivally (at the 2-3 o'clock position) with 1, 2, 5, or 25 mg/mL bevacizumab (Avastin; Roche Pharma, Basel, Switzerland; 5 lL per eye) one, two, or four times (injection every 2 days). For the recovery experiment, mice were injected simultaneously with bevacizumab (5 mg/ mL) and recombinant mouse pigment epithelium-derived factor (PEDF; R&D, San Diego, CA, USA; 15 ng/lL, 5 lL per eye), nerve growth factor (NGF; R&D; 20 ng/lL, 5 lL per eye) or ciliary neurotrophic factor (CNTF; R&D; 10 ng/lL, 5 lL per eye), in accordance with previous reports [32][33][34] and our preliminary experiments. Normal saline (0.9% NaCl) was injected as vehicle control.…”
Section: Methods and Materials Subconjunctival Bevacizumab Injection mentioning
confidence: 89%
“…Our results indicate that SalB blocks the CMS-induced increases in apoptosis in both the hippocampus and cortex and prevents the decrease of hippocampal volume and cell density. Interestingly, activated microglia were recruited into the regions of apoptosis and a significant correlation between apoptosis and microglial activation was observed both in the hippocampus and cortex, thereby indicating that CMS-induced apoptosis is associated with a microglia-mediated pro-inflammatory response [49] . Moreover, we observed that apoptotic cells were phagocytized by activated microglia, which suggests that microglia plays a dual role in the phagocytosis of apoptotic cells and the regulation of neuroinflammation.…”
Section: Discussionmentioning
confidence: 97%
“…The research on cellular and molecular mechanisms underlying learning impairment in MHE is currently underway. Proinflammatory molecules (such as TNF-α) can interact with each other to evoke apoptosis and tissue damage, resulting in retinal degeneration [47].…”
Section: Discussionmentioning
confidence: 99%